PESAN DAKWAH DALAM PODCAST LOG IN DI CLOSE THE DOOR PADA YOUTUBE DEDDY CORBUZIER - Mukhlizar; Hendri Efiadi; Miswanti; Eti Efrina (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2025)
Islam is a religion that encourages its followers to always do good deeds that are beneficial to many people and prevent bad deeds that harm themselves and others. With the advancement of science and technology, preaching has become easier for anyone to do through various media. The use of modern communication media must be utilized to convey preaching messages effectively and on target. This study aims to reveal the preaching messages contained in the Podcast Log In at Close The Door on Youtube Deddy Corbuzier episode 21. The theory used in this study is the theory of Endang Saipudin Ashari's preaching message and the theory of content analysis pioneered by Harold D. Lasswell. In this study, the researcher used a descriptive qualitative approach using the content analysis method. Based on the results of the study from the broadcast of episode 21 in the podcast log in at close the door, the researcher found 6 preaching messages which were divided into 3 categories, namely the message of faith, 1, namely Islam as a religion rahmatan lil alamin. The message of sharia, 1, namely the law of consuming pork. The message of morality, 4, namely politeness, Muslims are brothers, humble, following the sunnah. Keywords: Message, Preaching, Podcast, Youtube